Synergistic Effects in CNTs-PdAu/Pt Trimetallic Nanoparticles with High Electrocatalytic Activity and Stability - Cai, Xin-Lei; Liu, Chang-Hai; Liu, Jie; Lu, Ying; Zhong, Ya-Nan; Nie, Kai-Qi; Xu, Jian-Long; Gao, Xu; Sun, Xu-Hui; Wang, Sui-Dong (Nano-Micro Letters, 2017)
We present a straightforward physical approach for synthesizing multiwalled carbon nanotubes (CNTs)-PdAu/Pt trimetallic nanoparticles (NPs), which allows predesign and control of the metal compositional ratio by simply adjusting the sputtering targets and conditions. The small-sized CNTs-PdAu/Pt NPs ( 3 nm, Pd/Au/Pt ratio of 3:1:2) act as nanocatalysts for the methanol oxidation reaction (MOR), showing excellent performance with electrocatalytic peak current of 4.4 A mg −1Pt and high stability over 7000 s. The electrocatalytic activity and stability of the PdAu/Pt trimetallic NPs are much superior to those of the corresponding Pd/Pt and Au/Pt bimetallic NPs, as well as a commercial Pt/C catalyst. Systematic investigation of the microscopic, crystalline, and electronic structure of the PdAu/Pt NPs reveals alloying and charge redistribution in the PdAu/Pt NPs, which are responsible for the promotion of the electrocatalytic performance. Highlights: 1 CNTs-PdAu/Pt trimetallic nanoparticles (NPs, 3 nm) were synthesized using a straightforward physical approach of RTILs-assisted sputtering deposition. 2 As a high-performance nanocatalyst for the methanol oxidation reaction (MOR), CNTs-PdAu/Pt NPs show an electrocatalytic peak current of up to 4.4 A mg −1Pt and high stability over 7000 s, which is much superior to those of Pt-based bimetallic NPs and a commercial Pt/C catalyst. The optimal atomic ratio of Pd/Au/Pt, which has the best catalytic performance, was found to be 3:1:2. 3 Synergistic effects arose from charge redistribution among Pd, Au, and Pt in CNTs-PdAu/Pt NPs may be responsible for the promotion of the electrocatalytic activity.